1998
DOI: 10.1080/135475098231237
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the N acetyltransferase 1 NAT1 gene and lung cancer risk in a minority population

Abstract: One of the most consistently observed exposure-disease relationship is the one between cigarette smoking and lung cancer. Aromatic amines and their metabolites are found in tobacco smoke and may be a class of carcinogen involved in lung carcinogenesis. T he human N -acetyltransferase 1 (NAT 1) enzyme can activate or deactivate aromatic amines, making it a candidate genetic susceptibility gene. We evaluated the potential role of the NAT 1 gene in lung cancer risk in a hospital-based case-control study in a mino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…NAT1, although previously not proven [138], was recently also found to be associated with increased risk of AC in Caucasian population. Interestingly, the AC risk was further increased in subjects with unfavourable combination of NAT1 fast and NAT2 slow acetylator genotypes.…”
Section: N-acetyltransferasesmentioning
confidence: 94%
“…NAT1, although previously not proven [138], was recently also found to be associated with increased risk of AC in Caucasian population. Interestingly, the AC risk was further increased in subjects with unfavourable combination of NAT1 fast and NAT2 slow acetylator genotypes.…”
Section: N-acetyltransferasesmentioning
confidence: 94%
“…DNA sequence variations, including m1 (T6235C in the 3’‐flanking region, commonly referred to as MspI polymorphism), m2 (A4889G at exon 7), m3 (T5639C in the 3’‐flanking region), and m4 (C4887A at exon 7), are found to be common and associated with cigarette smoking‐related cancer risk [72, 75, 87, 136151]. The CYP1A1 Msp I genotype is associated with lung cancer risk in light smokers [143] in which higher CYP1A1 inducibility or enhanced catalytic activity was found in rare allele carriers when they smoked moderately. Mechanisms for the interaction between smoking and CYP1A1 could be at the level of gene expression or enzyme activity [152, 153].…”
Section: Tobacco‐gene Interaction and Pancreatic Cancermentioning
confidence: 99%
“…Individual studies may be underpowered, since the CYP1A1 polymorphisms, which are relatively common in Japan (30% of population), are much less common in Europeans and North Americans (o10% of population) (Warren and Shields, 1997). While a study of African-Americans and Mexican-Americans showed a twofold increased risk of lung cancer among light smokers with the MspI variant genotype (Ishibe et al, 1997), a Brazilian study showed increased risk with the Ile-Val polymorphism and not the MspI polymorphism (Hamada et al, 1995). Reports from Norway and Finland show a lack of association of either of the CYP1A1 polymorphisms with lung cancer risk (Tefre et al, 1991;Hirvonen et al, 1992).…”
Section: Carcinogen Metabolismmentioning
confidence: 99%